2023
DOI: 10.21203/rs.3.rs-2452500/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of gastrointestinal symptoms and skipping breakfast on anxiety and depression in quarantined Chinese college students during the COVID-19 pandemic: A cross sectional survey

Abstract: Background: Strict quarantine is an effective measure to prevent the spread of the Coronavirus disease (COVID-19) pandemic, but it probably increases the risk of anxiety and depression. We aimed to evaluate the anxiety and depression among quarantined college students at school during the COVID-19 pandemic and investigate whether gastrointestinal discomfort related-factors and skipping breakfast lead to increased risk of anxiety and depression. Methods: 384 quarantined college students in Shanghai China were r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The psychological consequences of long COVID were compared between different groups, such as school-going adolescents, COVID-19 survivors, and their relatives, indicating a widespread impact on mental health [96][97][98][99]. The psychological state of college students was found to be more vulnerable to the outbreak of COVID-19 than other groups [100]. Additionally, the existing literature on the mental health consequences of the pandemic on both the general population and persons with confirmed COVID-19 showed that depression, anxiety, and other mental health problems are common [101].…”
Section: Psychological and Social Consequences Of Long Covidmentioning
confidence: 99%
“…The psychological consequences of long COVID were compared between different groups, such as school-going adolescents, COVID-19 survivors, and their relatives, indicating a widespread impact on mental health [96][97][98][99]. The psychological state of college students was found to be more vulnerable to the outbreak of COVID-19 than other groups [100]. Additionally, the existing literature on the mental health consequences of the pandemic on both the general population and persons with confirmed COVID-19 showed that depression, anxiety, and other mental health problems are common [101].…”
Section: Psychological and Social Consequences Of Long Covidmentioning
confidence: 99%